The Influence of Entrepreneurship Education and Self-Efficacy on Students' Entrepreneurial Interest : A Case Study on Students of Tunas Pembangunan University of Surakarta - Nabilla Aisyah Nori; Supartini Supartini; Syahriar Abdullah (International Journal Business, Management and Innovation Review, 2025)
Entrepreneurship plays a significant role in driving the Indonesian economy. However, the main challenge in the country is the relatively low number of entrepreneurs. To foster an interest in entrepreneurship and enable individuals to successfully manage their businesses, a variety of factors must encourage aspiring entrepreneurs. Therefore, this study seeks to explore the impact of: (1) Entrepreneurship Education; and (2) Self-efficacy to students' entrepreneurial interests at Tunas Pembangunan University Surakarta. This study refers to the findings of Fan, et.al., (2024) and Rahmadani, et.al., (2023). Using a quantitative approach, the data analysis will use multiple linear regression techniques with SPSS version 25 as the analysis tool. Primary data for this study were collected through an online questionnaire distributed through Google From, using the purposive sampling method. This research was conducted at Tunas Pembangunan University of Surakarta, with a sample of 140 students of Tunas Pembangunan Surakarta University with the criteria of having taken entrepreneurship courses, participating in programs related to entrepreneurship or owning a business and running a business. The findings of this study show that, according to the T-test, entrepreneurship education and self-efficacy partially influence entrepreneurial interest. Furthermore, the F-test revealed that these two variables collectively affect entrepreneurial interest. In addition, the R2 determination coefficient test showed an Adjusted R Square value of 66.4%, which showed that the remaining 33.6% was influenced by other variables that were not studied in this study.